Edukasi dan Penyuluhan Sebagai Upaya Peningkatan Kesehatan Masyarakat di Dusun Kadiluwih - Nawangsari, Meita; Salam, Abdullah Faizurrahman; Ahmad, Alif Arsyaduddin; Rahmawati, Yeni; Az-zahra, Fathih Aqidhatul; Annisah K P, Putik Alaeyda; Firmansyah, Riffat; Rihhadatul ‘Aisy, Zaki; Salma, Shabrina Aulia; Purwoko, Akhmad Edy (Universitas Muhammadiyah Yogyakarta, 2025)
Hypertension and diabetes are diseases that are prevalent among the people of Kadiluwih regency, with a high history of stroke and heart attack cases. The main risk factors include unhealthy diet, physical inactivity, obesity and genetic factors. Low awareness of early detection exacerbates this condition. To overcome these problems, this community service program (PKM) aims to increase public awareness and knowledge about noncommunicable diseases (NCDs) and encourage the implementation of healthy lifestyles to reduce the number of complications. The activities carried out include family care, counseling on non- communicable diseases, DAGUSIBU (Get, Use, Store, Dispose of medicines properly) education, and education and cultivation of family medicinal plants (TOGA). The methods used included counseling, mentoring, and health checks. Initially, many participants did not understand the risk factors for hypertension and diabetes and how to prevent them, but after the education, the majority of participants showed a better understanding and were able to re-explain the information provided. With this positive response, it is hoped that the program can have a lasting impact on increasing health awareness and promoting healthy living in the Kadiluwih district.